Fry Bread : A Native American Family Story - Maillard, Kevin Noble; Martinez-Neal, Juana (New York : Roaring Brook Press, 2019)
Depicts a modern Native American family in their daily life.
Includes bibliographical references.
Keywords: Indians of North America -- Juvenile fiction; Families -- Fiction; Indians of North America -- Fiction; Family life -- Fiction